Hall of Heroes: A Digital Game for Social Skills Training with Young Adolescents. (1st January 2019) - DeRosier, Melissa E.; Thomas, James M.
Abstract : Traditional social skills training (SST) programs are delivered in person and suffer from significant time, financial, and opportunity barriers that limit their reach and potential benefits for youth. This paper describes the design and preliminary evaluation of Hall of Heroes, a digital game that presents SST through an engaging superhero-themed virtual story world. Participants were randomly assigned to complete the digital game (n = 15) or to a waitlist control condition (n = 14) and were compared on parent-report measures of social emotional functioning. Youth who completed Hall of Heroes significantly improved in their abilities to relate to others (both peers and family members) as well as to accept affection and express emotions with others, compared to youth who did not complete the SST intervention. Further, youth in the treatment condition showed a significantly greater decline in feelings of anxiety, depression, and hopelessness than did youth in the control condition. Both parents and youth reported high levels of engagement in and acceptability of the Hall of Heroes . This study adds to the research literature, supporting the potential of a game-based SST platform for effectively helping youth develop prosocial social problem-solving skills.